2022
DOI: 10.3389/fpubh.2022.938423
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on the prevalence and risk factors of workplace violence among healthcare workers in China

Abstract: BackgroundThe pandemic of COVID-19 has significantly increased the burden on healthcare workers and potentially affect their risk of workplace violence (WPV). This study aimed to explore the prevalence and risk factors of WPV among healthcare workers during the peaking and the remission of the COVID-19 pandemic in China.MethodsUsing the snowball method, a repeated online questionnaire survey was conducted among Chinese healthcare workers from March 27th to April 26th in 2020 and 2021, respectively. Data includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 54 publications
0
17
1
3
Order By: Relevance
“…In the present study, the prevalence of workplace violence was at a high level and was 64.2%, 53.2%, and 50.5% for wave 1, wave 2, and wave 3, respectively. A previous study found that workplace violence against health professionals decreased as the pandemic continued in mainland China ( 29 ). Studies have found that workplace violence triggered burnout among HPs ( 29 , 43 ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the present study, the prevalence of workplace violence was at a high level and was 64.2%, 53.2%, and 50.5% for wave 1, wave 2, and wave 3, respectively. A previous study found that workplace violence against health professionals decreased as the pandemic continued in mainland China ( 29 ). Studies have found that workplace violence triggered burnout among HPs ( 29 , 43 ).…”
Section: Discussionmentioning
confidence: 98%
“…A previous study found that workplace violence against health professionals decreased as the pandemic continued in mainland China ( 29 ). Studies have found that workplace violence triggered burnout among HPs ( 29 , 43 ). Saifur also found workplace violence-exposed nurses were at a greater risk of burnout during the COVID-19 pandemic ( 44 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The percentage of emergency physicians experiencing any type of WPV was greatly higher than the overall prevalence of WPV against Chinese ED clinicians during the COVID-19 pandemic (29.2%) [ 19 ]. Similarly, the prevalence of WPV against Chinese HCWs decreased after the COVID-19 pandemic [ 23 , 24 ]. The improved doctor–patient relationship and doctor–patient trust during the COVID-19 pandemic may interpret the variation to some degree [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this difference is that, in contrast to the present data, none of those studies compared data on the incidence of WPA before and during the pandemic. However, a recent study analyzing data from 2020 and 2021 also found a decrease in the prevalence of WPA among HCWs the year after the onset of the pandemic ( 20 ).…”
Section: Discussionmentioning
confidence: 99%